Storey's Guide to Keeping Honey Bees: Honey Production, Pollination, Bee Health - Sanford, Malcolm T.; 1942-; (Malcolm Thomas); Bonney, Richard E. (North Adams, MA, 2018)
"[This guide] ... presents comprehensive yet accessible information on everything from planning hives and installing a colony to preventing disease and managing productive hives that will bear bountiful honey harvests year after year"--Amazon.com.
Beginning beekeeping -- Origin and history of beekeeping -- A bee's life -- Choosing hive location -- Getting equipped -- Enter the bees -- Managing honey bee colonies -- Taking the crop -- Pollination -- Diseases and pests of the honey bee -- Additional strategies.
Includes bibliographical references (pages 202-204) and index.
Keywords: Honeybee; Bee culture